Preparation, Growth, and Magnetic Properties of Co-doped Yb2O3 Nanoparticles and Thin Films by the Sol-Gel Process - (:unkn) unknown (SPRINGER, 2012)
In this study, the preparation, growth, structure and magnetic properties of Co-doped Yb2O3 (with the Co concentration of x=0.2) nanoparticles and thin films are studied. Precursor solutions were prepared by using the sol-gel synthesis process to produce nanoparticles and thin films. Co-doped Yb2O3 thin films with different thickness were produced on Si(100) substrate using the sol-gel dip coating procedure. The particle size and the crystal structure of nanoparticles were ascertained by X-ray diffraction and Scanning Electron Microscope. The surface morphologies and the microstructure of all samples were investigated by means of the Scanning Electron Microscope and the X-ray diffraction. A Quantum Design PPMS was used for magnetic measurements. Surface morphologies of Co-doped Yb2O3 thin films were found to be dense, without porosity, uniform, and devoid of cracks and pinholes. The grain size and thin-film thickness of Co-doped Yb2O3 were determined to be approximately 50 nm and 84 nm, respectively.
Keywords: Nanoparticles; Magnetic measurement; Sol-gel; Rare-earth sesquioxides; X-RAY-DIFFRACTION; OPTICAL-PROPERTIES; TEMPERATURE; MICROSTRUCTURE; POWDER